Promoting 21st century skills in Higher Education through collaboration and activities - Ilaria Bortolotti; Donatella Cesareni; Nadia Sansone (Firenze University Press, 2018)
The paper presents a model of university teaching where students are involved in concrete activities and collaborate while developing key competences for the academic and working future. 52 students of the Degree Course in Psychology at the Sapienza University of Rome participated to the activity. The method of data collection and analysis combines qualitative and quantitative approach. Results show a general perception of skills enhancement and a good appreciation of the course, especially in comparison with traditional learning modes
Keywords: skills; technologies; collaborative learning; project-based learning